The Effectiveness of Psychoeducation on Reducing the Significance of Mania Symptoms and Increasing the Insights among the Patients with Bipolar I Disorder in Mania Phase - Afshin Saberi; Mortaza Tarkhan; Alireza Agha-Yousofi; Hosein Zare (مجله دانشکده پزشکی اصفهان, 2018)
Background: The purpose of this study was to evaluate the effectiveness of psychoeducation on increasing insight and reducing mania symptoms in patients with bipolar I disorder in mania phase.